Mechanisms and regulatory pathways of recessive land use transition - TAN Lin, CHEN Lan (Ziyuan Kexue)
[Objective] The study of recessive land use forms is a crucial aspect of land use research. Clarifying the scientific connotation and intrinsic mechanisms of recessive land use transition and exploring regulatory pathways to address urban-rural economic and social transitions can provide a basis for optimizing territorial spatial patterns and promoting high-quality development. [Methods] Based on the improved social development model, we constructed a framework for the mechanisms of recessive land use transition. We employed logical deduction and literature analysis to examine the conceptual connotation of recessive land use forms and their transition pathways. [Results] (1) The trinity framework of “power form - functional form - efficiency form” reflects the basic pattern of recessive land use forms within a region. The power form regulates the efficiency form, and the efficiency form reflects the power form; the power form is the fundamental basis of the functional form, while the functional form is the driving force of the power form; the functional form is the key support of the efficiency form, and the efficiency form is the external manifestation of the functional form. These three forms are closely interconnected and interact with each other. (2) Implicit land use transition is the process of significant and fundamental changes in efficiency, functional, and power forms. It is rooted in the intervention system composed of regional resource endowments, engineering and technological systems, policy and institutional environments, cultural value recognition, and socio-economic development, featuring inherent relevance and dynamic adjustability. (3) Based on the underlying logic of “comprehensive land benefits - dominant land functions - land development rights”, regulatory pathways with element-coordinated governance, classification-based management guidelines, and well-improved institutional structure are constructed, which facilitate recessive land use transition. [Conclusion] Taking into account of precisely capturing the characteristics of recessive land use form changes over various periods, timely measuring and diagnosing spatial conflict inflection points, identifing regulatory points, and coordinating the actual demands of power, functional, and efficiency forms, recessive land use regulatory schemes suitable for specific levels of economic and social development are developed.